Territorial and Linguistic Demarcations in the Dispositif Kärnten/Koroška - Peball, Roland W.; Schoenberger, Klaus (Traditiones, 2022)
In southern Carinthia (Kärnten/Koroška), a conflict over the rights and oppression of the Slovenian-speaking minority has been smoldering for one hundred years, since the military border conflict of 1918/19 and the plebiscite agreed upon in the Treaty of St. Germain. The plebiscite was on the question of whether southern Carinthia should join the rump state of the former Habsburg monarchy, German-Austria, or the newly created SHS. In 1920, the majority of the resident population (both the German Carinthians and the Slovenian minority) decided in favor of Austria. In the following decades an unrelenting struggle for language and memory was waged by German-nationalist-minded representatives of the German Carinthian majority against the minority. This article analyzes the thematization of linguistic and territorial demarcations in the dispositif Kärnten/Koroška.